El concepto de justicia en Leibniz - Di Castro, Elisabetta (2014)
This article analyzes the concept of justice in Leibniz, emphasizing universal justice understood as the search of common happiness without violating one`s own happiness, His position can be seen as a republican thesis which shelters pluralism and harmonizes one’s own good with the common good.